(untitled) (Revista Nacional de Odontología, 2015)
Introduction: This study’s main goal was to describe the oral status of 3 to 5-year-old children from Las Golondrinas Kindergarten, Carpinelo branch, in Medellín, according to some social demographic variables. Methods: descriptive study in 93 children from 3 to 5 years old. Clinical evaluation under international parameters was performed. Social demographic variables of children and their parents were analyzed, as well as the Simplified Oral Hygiene Index (ohi-s), prevalence and experience with tooth decay in primary teeth by the traditional and modified ceo index, Significant Caries Index (SiC) and treatment needs. Univariate and bivariate analysis and Chi Square Tests to determine significant differences among the variables. Results: a prevalence of tooth decay in primary teeth of 59% and experience of 61% were reported when all the caries lesions are included, with a modified ceo-d average of 3.41 (+4.27). This indicator increases when the Sic (8.5) is calculated. The average OHI-S is of 1.36 (IC 95% 1.10-1.62), reporting levels of regular hygieneof 68.8% of the cases, and bad hygiene in 9.7%. There were differences in the indicators, according to social demographic characteristics. There were mediate needs for dental treatment in the studied population, especially dental fillings, sealants and fluoride varnish. Conclusion: there were differences in the analyzed indicators according to social demographic factors, as well as population subgroups, proving inequality in the incidence of tooth decay. Strategies and policies for the wellbeing in the early childhood are required.